Analysis of Dance Extracurricular Activities at Pertiwi Kindergarten Medan - Enjelina Vincere Sihombing; Wan Nova Listia (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the implementation of dance extracurricular activities in early childhood education within the framework of the Merdeka Curriculum. Early Childhood Education (ECE) emphasizes play-based learning supported by a flexible curriculum that accommodates children's developmental needs. Extracurricular activities, particularly dance, play a significant role in fostering children's creativity, motor skills, and self-confidence. This research employs a descriptive qualitative approach conducted at TK Pertiwi Medan. Data were collected through observations and interviews with teachers and the school principal to examine the planning, organizing, implementation, and evaluation of dance extracurricular activities. The findings reveal that the implementation of dance extracurricular activities has been carried out effectively in practice, particularly in terms of teaching methods using demonstrations and repetitive exercises adapted to children's abilities. However, the program is not yet supported by systematic administrative management. Planning is conducted flexibly without written teaching modules, organizational structures are informal, and evaluation is carried out through direct observation without standardized assessment instruments or documentation. Despite these limitations, the program has successfully contributed to students’ achievements, as evidenced by consistent victories in dance competitions over the past four years. This indicates that practical implementation and teacher competence play a crucial role in program success, although improvements in structured planning, organization, and evaluation are still needed to optimize educational outcomes.